Prevalence of multidrug resistance (MDR) and extended spectrum beta-lactamases (ESBLs) among uropathogenic Escherichia coli isolates from female patients in a tertiary care hospital in North India - Das, Bhaskar; Mittal, Natasha; Goswami, Rajni; Adhana, Deepti; Rathore, Neha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Urinary tract infection (UTI) is a common bacterial infection in women. It is very common during pregnancy and may present as asymptomatic bacteriuria. Escherichia coli is the primary urinary pathogen accounting for 74-90% of uncomplicated urinary tract infection. The aim of the study was to evaluate in-vitro antibiotic susceptibility among urine isolates of Escherichia coli and prevalence of resistance marker like ESBL producer and MDR status. Methods: Mid-stream urine samples of 205 female patients were processed for culture and sensitivity. All the samples were inoculated on culture media and growth showing significant bacteriuria (>105 cfu/ml) were subjected to identification and antibiotic sensitivity testing on Automated system BD Phoenix 100. ESBL status was detected by the system and MDR status was evaluated by standard guidelines. Results: Out of 205 urine samples, 47 samples (22.93%) showed growth of organism. Out of the 47 growth positive samples, 36 (76.60%) samples showed growth of Escherichia coli and out of which 13 (36.11%) were ESBL producer and 23 (63.89%) were ESBL non-producer. Escherichia coli was mostly isolated from younger age group (21-40 years) (61.11%). Antimicrobial susceptibility showed very good sensitivity towards Amikacin, Tigecycline, Carbapenems, Fosfomycin, Piperacillin-tazobactam and Nitrofurantoin. All the isolates of ESBL producer are MDR (100%) and 21.7% of ESBL non-producer are MDR. There is evidence of transfer of resistance genes for non-β-lactam antibiotics along with ESBL resistance marker. Conclusions: Escherichia coli was the predominant uropathogen isolated from female patients and Amikacin, Nitrofurantoin and Fosfomycin can be used as first line drug.